Raising empowered athletes : a youth sports parenting guide for raising happy, brave, and resilient kids - Jones, Kirsten (Motivational speaker) (Triumph Books, 2023)
"Today's youth sports experience provokes countless questions for well-intentioned parents. How young should kids start playing sports? Should they specialize-and when? What should a parent do when their kid is not getting the playing time they think their child deserves? How do parents encourage children without overwhelming them? And most importantly: how do we ensure our kids both reach their true potential on the playing field, and are well-prepared to be successful in life? Raising Empowered Athletes has answers for every youth sports situation with an overarching goal of not only helping parents raise strong athletes, but nurture great human beings who are empowered to succeed on and off the playing field. Nationally recognized performance coach Kirsten Jones-a former Division I athlete herself-covers wide-ranging topics including the origins of today's hyper-competitive environment, what to insist on for your child's earliest sports experiences, club and travel teams, best approaches to family conversations and goal-setting, and the transition to high school sports"--